Heifer synchronization using 7-11 synch or 7-11 synch + CIDR - Eborn, D.R.; Spiker, C.R.; Sullivan, R.R.; Grieger, David M. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2009)
Two aims of heifer estrus synchronization protocols are to induce prepubertal heifers to start cycling by the beginning of the breeding season and to shorten time spent in estrous detection. Use of progestins such as melengestrol acetate (MGA) and intravaginal progesterone-releasing devices (CIDR) can induce prepubertal heifers to begin cycling as well as synchronize estrus in cycling heifers. In past years, a timed artificial insemination protocol (7-11 COSynch) has been tested with varying results. Pregnancy rates using 7-11 COSynch have typically ranged from 40 to 60%. The objective of the current trial was to determine the effect of a similar heat-detection protocol (7-11 Synch) with or without a CIDR. We compared heat response, interval to estrus, and conception rates in beef heifers.
Keywords: Beef; Cattle; CIDR; MGA